Problemas de Otimização Quase Convexos: Método do Gradiente para Funções Escalares e Vetoriais - SANTOS, Milton Gabriel Garcia dos (2011)
This work we study the convergence properties of the Gradient Method Designed and Descent Method for Multi-objective optimization. At first, our optimization problem is to minimize a real function of n-variables, continuously differentiable and restricted to a set of simple structure and add on the objective function of the hypothesis of pseudo-convexity or quasi-convexity. Then we consider the problem of unconstrained multi-objective optimization and add some hypotheses about the function vector, such as convexity or quasi-convexity, and is continuously differentiable. It is noteworthy that in both problems will be used to search for inexact Armijo over viable directions.